Optimalisasi Sistem Online Single Submission pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Terhadap Usaha Mikro Kecil Kota Lubuklinggau - Yanti, Fitri; Lestari, Umi Fitriana (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to determine the optimization of the Online Single Submission (OSS) system at the Investment and One-Stop Integrated Service Office for Micro and Small Enterprises in Lubuklinggau City and the factors that hinder it. This research uses a descriptive qualitative method intended to provide a clear and comprehensive depiction with assured accuracy of the existing issues. Data collection was carried out through observation, interviews, and documentation. The research results indicate that the optimization of the OSS system at the Investment and One-Stop Integrated Service Office for Micro and Small Enterprises in Lubuklinggau City has been quite optimal because: 1) Communication within OSS through socialization to the public regarding OSS and communication from OSS operators and the Investment and One-Stop Integrated Service Office has been good, as business actors are given explanations on the requirements for processing until the business identification number (NIB) is issued, in line with the vision and mission of the Investment and One-Stop Integrated Service Office; 2) The resources (operators) tasked with operating the OSS application system number two people, as OSS services do not take a long time because when all requirements have been fulfilled by business actors, the service can be quickly completed, supported by facilities and infrastructure such as computers, printers, and internet networks; 3) The disposition or attitude and commitment of the Investment and One-Stop Integrated Service Office have been quite good.